A large facility for photosensors test at cryogenic temperature. (1st March 2023) - Balmforth, Z.; Basco, A.; Boiano, A.; Canci, N.; de Asmundis, R.; Di Capua, F.; Fiorillo, G.; Grauso, G.; Matteucci, G.; Pandalone, A.; Sandford, E.; Suvorov, Y.; et al.
Abstract: Current generation of detectors using noble gases in liquid phase for direct dark matter search and neutrino physics need large area photosensors. Silicon based photo-detectors are innovative light collecting devices and represent a successful technology in these research fields. The DarkSide collaboration started a dedicated development and customization of SiPM technology for its specific needs resulting in the design, production and assembly of large surface modules of 20 × 20 cm 2 named Photo Detection Unit for the DarkSide-20k experiment. Production of a large number of such devices, as needed to cover about 20 m 2 of active surface inside the DarkSide-20k detector, requires a robust testing and validation process. In order to match this requirement a dedicated test facility for photosensors was designed and commissioned at INFN-Naples laboratory. The first commissioning test was successfully performed in 2021. Since then a number of testing campaigns were performed. Detailed description of the facility is reported as well as results of some tests.